After encounters: revealing patients' unseen work through their pathways to care. Issue 2 (6th May 2020) - Humphris, Rachel; Bradby, Hannah; Padilla, Beatriz; Phillimore, Jenny; Pemberton, Simon; Samerski, Silja
Abstract : Purpose: Research has long focused on the notion of access and the trajectory towards a healthcare encounter but has neglected what happens to patients after these initial encounters. This paper focuses attention on what happens after an initial healthcare encounter leading to a more nuanced understanding of how patients from a diverse range of backgrounds make sense of medical advice, how they mix this knowledge with other forms of information and how they make decisions about what to do next. Design/methodology/approach: Drawing on 160 in-depth interviews across four European countries the paper problematizes the notion of access; expands the definition of "decision partners"; and reframes the medical encounter as a journey, where one encounter leads to and informs the next. Findings: This approach reveals the significant unseen, unrecognised and unacknowledged work that patients undertake to solve their health concerns. Originality/value: De-centring the professional from the healthcare encounter allows us to understand why patients take particular pathways to care and how resources might be more appropriately leveraged to support both patients and professionals along this journey.